An experimental study on design and characterization of CO2 adsorbents - Acar, Burcu. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The aim of this study is to design and develop AC-based CO2 adsorbent(s) having both high and stable CO2 adsorption capacity, and ability to adsorb CO2 selectively from CO2-CH4 mixture. In this context, a commercial activated carbon, Norit ROX, was oxidized by air and HNO3 oxidation, and two series of adsorbents, AC8 and AC9 series, respectively, were prepared on those oxidized ACs by K2CO3 impregnation following by calcination at various temperatures. The adsorbent samples were characterized by SEM-EDX for analyzing their microstructural properties and alkali dispersion on their surface. The clusters formed on AC8 adsorbents were not homogeneously distributed over the adsorbent, whereas AC9 adsorbents had homogeneously dispersed K-formations on their surfaces. Adsorption/desorption and selective adsorption tests were conducted for 0-1000 mbar pressure range under 50 ml/min gas flow rate at room temperature (RT), 120 °C and 200 °C for pure CO2, pure CH4 and their mixtures, 50% CO2-50% CH4 and 10% CO2-90% CH4. The adsorption/selective adsorption performance of AC9 series, were inferior to the performance of the AC8 series adsorbents. The highest CO2 adsorption capacity, ca. 11 wt.%, was observed for AC8-300 sample at RT. CO2 adsorption was confirmed to be reversible, whereas CH4 adsorption was partially irreversible. Although AC8-200 has the highest mass based CO2:CH4 adsorption selectivity ratio, ca. 3.7, at RT for the 50% CO2-50% CH4 mixture, for the 10% CO2-90% CH4 mixture, mass based adsorption selectivity ratio was at its highest on AC8-250 with a value of 0.59. AC8-200 was further tested for 0-5000 mbar pressure range at RT under 50 ml/min pure CO2 and pure CH4 flow and 90 ml/min total flow of 50% CO2-50% CH4 and 10% CO2-90% CH4 gas mixtures. The CO2 adsorption capacity was measured as 19.7 wt.% at 5000 mbar. The experimental adsorption isotherm data were fitted to Langmuir, Freundlich and Dubinin-Radushkevich (D-R) models. D-R model was the most successful in explaining CO2 and CH4 adsorption behaviors of AC samples. Between the kinetic models, pseudo-first order kinetic model successfully explained both CO2 and CH4 adsorption kinetics at RT, whereas CH4 adsorption kinetics on AC8-200 and AC8-300 were more suitably explained by pseudo-second order kinetic model.
Keywords: Carbon -- Absorption and adsorption.